Comprensión del significado desde Vygotsky, Bruner y Gergen (2010)
This article is a product of the investigation "The meaning from Lev Semionovich Vygotsky, Jerome Bruner and Kenneth Gergen ". The pretension is to understand the concepts of "meaning" constructed by these authors, by means of the review of some of his works. The method of investigation used was the analysis of content; in addition, there was realized a goal - observation of this work of degree that allowed to establish new relations between the authors. The realized analysis allowed to discover differences and points of consensus between three authors, as for the definition of the meanings, the explanation of his origin and evolution and the delimiting of the functions that these fulfill in the human beings. Since original idea in Vygotsky highlights the step of the interpsychological meaning to the intrapsychologica; in Bruner, the constant negotiation of meanings between human immersed beings in a culture; and in Gergen, the relational construction of the meanings.